Development Strategy Analysis With IFE-EFE-IE Matrix, SWOT Matrix and AHP at PT Putra Morowali Sejahtera - Sibarani, Andreas; Djunita Pasaribu, Rina (International Journal of Science, Technology & Management, 2024)
Heavy equipment construction equipment usage activities are used for material handling, excavation, lifting, and other heavy operations. PT PMS currently does not have a strategy to face challenges in the heavy equipment rental business, this causes a lack of maximization of the heavy equipment rental business so that an analysis of internal and external factors is needed to determine a strategy for PT PMS. The purpose of this research is to identify internal (strength and weakness) and external (opportunity and threat) factors using the IFE and EFE approaches and using the IE and SWOT Matrix to determine alternative business strategies that can be recommended to PT PMS to choose the most appropriate business strategy used with Analytical Hierarchy Process (AHP) priorities to develop the heavy equipment rental business. The research method used in this research is qualitative. Qualitative research gets data from interviews with sources and scoring on a matrix based on a list of questions that have been provided. The results showed that the IFE matrix score was 3.03 and the EFE matrix score was 2.43, so that the position of PT Putra Morowali Sejahtera in the IE matrix was in cell IV, namely the growth and build strategy. From the results of the SWOT matrix, the company has 8 alternative strategies. The 8 alternative strategies are then evaluated in the AHP matrix to determine priority or ranking. The recommended strategy for PT Putra Morowali Sejahtera according to the ranking in the AHP matrix is ranking 1 Improving the quality of heavy equipment rental services and increasing the efficiency and effectiveness of operational activities in order to provide services at more competitive prices, ranking 2 Continuous improvement to expand the heavy equipment rental market network and increase operational effectiveness and efficiency, and ranking 3 Increase the capacity of heavy equipment rental units to meet demand for heavy equipment usage. The strategy is expected to contribute to the development of PT Putra Morowali Sejahtera.